Activating Mutation in the Receptor Tyrosine Kinase FLT3 with Clinicopathological Relevance in Canine Mast Cell Tumors - Nawin Manachai; Kasem Rattanapinyopituk; Piyanoot Fonghem; Panrawee Phoomvuthisarn; Shingo Nakahata; Kazuhiro Morishita; Anudep Rungsipipat (Veterinary Medicine International)
Recent research has focused on the receptor tyrosine kinase (RTK) KIT which is involved in the pathogenesis of canine mast cell tumors (MCT). However, the role of other RTKs in this neoplasm remains unclear. The present study aimed to determine the frequency of FLT3 mutations and to evaluate the mutational status and clinicopathological relevance of canine MCT patients. There were a total of 20 cases that were cytologically and histopathological diagnosed as canine MCTs; genomic polymerase chain reaction (PCR) and Sanger sequencing were used to identify mutations. For the juxtamembrane (JM) domain, the FLT3 14/15 primer pair was used to investigate exon 14/15 loci. Based on genomic PCR amplification of exon 14/15 and 20 of the FLT3 gene and Sanger sequencing of 20 cases of canine MCTs, the overall frequency of FLT3 mutation in canine MCTs was 75%. The majority of FLT3 mutations (70%) were internal tandem duplications (ITD) of the JM domain, while one case arose from deletion mutations of the tyrosine kinase domain (TKD). However, double mutations were not observed in this study. Furthermore, there is also clinicopathological relevance to MCT dogs carrying FLT3-ITD mutations, showing a tendency toward leukocytosis due to neutrophilia, and resembling human acute myeloid leukemia (AML) with FLT3-ITD mutations. A subset of MCTs with FLT3-ITD mutations, showing an enhanced signal of phosphorylated ERK1/2 identified by immunoblotting, suggests that an activating mutation may be driven by a distinct signal of the ERK pathway. Our results indicate that FLT3-ITD mutation is an oncogenic driver of canine MCTs, and that it shares some clinicopathologic features with human AML. These findings may offer new opportunities for further studies on canine mast cell tumorigenesis and a novel therapeutic target for canine MCT cases harboring FLT3-ITD mutations.